Moho depth and equivalent elastic thickness of the lithosphere over the Vema Channel: A new evidence of an aborted ridge - Constantino, Renata Regina [UNESP]; Costa, Iago Sousa Lima; Hackspacher, Peter Christian [UNESP]; de Souza, Iata Anderson [UNESP] (Elsevier, 2018)
We investigate the Vema Channel in terms of spatial variations of the elastic thickness (Te) in the frame of the thin plate flexure model using the convolutive method. The modeling of the Moho in terms of the thin plate flexure model is done by a least squares approximation of the Moho obtained from gravity inversion. The flexure is calculated by the convolution of the crustal load with the point-load flexure response curves. The RMS difference between the gravity and flexure Moho surfaces is minimized by varying the Te by inverse modeling. The result is a solution of the flexed crust that is in best agreement with the long-wavelength component of the gravity field. The flexure Moho depths vary between 12 and 18 km and agree well with those obtained from gravity inversion. The spatial variations of Te range from 2 to 30 km and have a good correlation with the geological interpretation for an aborted ridge near Vema Channel, called in this paper as the Vema Aborted Ridge (VAR). The occurring of seamounts appears to be correlated to a weak and deformed region. Attempts of crustal breakup are marked by high Te values (30 km) while lower values (3–12 km) are found for the suggested aborted ridge. The VAR is on Isochron of 93 Ma and shows symmetrical older along both sides of its axis. Asymmetric magnetic anomalies are found over the ridge and may be related to upper-extended continental crust broken by the Vema.
Keywords: Aborted ridge; Extinct spreading center; Flexural analysis; Flexural rigidity; South Atlantic evolution